Survey of the influence of factors affecting the receipt of taxes from the big taxpayers in Sistan and Baluchestan province: Logit and Probit Approach - Reza Roshan; Parviz Hajiani (International Journal of Business and Development Studies)
In this article, the impact of various factors such as whether the company is public or private, certificate of clearance and the company's income on the paying tax situation by 57 large companies in the Sistan and Baluchistan province, has been investigated. Since the dependent variable of tax collection is a binary variable, probit and logit models have been used to estimate the coefficients. The results of using two models show that all three explanatory variables have a positive and significant effect on tax payment by companies. And the biggest effect is related to the certificate of clearance, state of the company, and company's income, respectively. Examining the final effects also shows that as the company's income increases, the probability of paying its taxes has decreased and this is because the company with a larger income pays taxes on time and better because of the fear of the consequences of not paying taxes and also knowing with the rules of paying taxes. Therefore, with the increase in income, the probability of paying the company tax also increases less. The Hosmer-Lemshow statistic also indicates that the models fit well and the model is consistent with the data. It is suggested that the laws be amended in such a way that it is necessary for the companies to complete the accounts so that the government can collect taxes from more companies through this law. and limit the way of tax evasion.